Strategy for Developing Student Dakwah Competencies in the Field Dakwah Training Program at MTs Al-Mu'min Muhammadiyah Tembarak - Fakhrudin, Fakhrudin; Haris, Abdul; Yazid, Syamsurizal (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to describe the standards of student da'wah competency at MTs Al-Mu'min Muhammadiyah Tembarak as well as their development strategies in the Field Da'wah Training (PDL) program. This research was carried out using a qualitative approach with a case study type, where data was collected through observation, interviews and documentation. The validity of the data is tested using source triangulation techniques, while data analysis is carried out through the stages of data condensation, data presentation, and conclusion drawing. The research results show that MTs Al-Mu'min Muhammadiyah Tembarak has developed student missionary competency standards and development strategies comprehensively, through an integrative approach between theory and practice. The competency standards developed include a correct understanding of religion which is internalized in the activities of the call to prayer, congregational prayer, cult, dawn lectures and teaching TPQ; be an MC at an event; have moral character; able to understand the internalized environment through being active in social activities; and self-control in the form of discipline as substantive competence. Furthermore, the ability to plan, implement and evaluate various designed activities becomes part of the methodological competence developed. The strategy for developing students' da'wah competence at MTs Al-Mu'min Muhammadiyah Tembarak is outlined in four forms of activities, namely presentation of da'wah fiqh subjects, muhadloron familiarization, micro teaching practice, and debriefing carried out before departure to the PDL location.